Development of battery charger for PV systems - Jiang, Jun (2014)
Nowadays, with the increasing development of a stand-alone photovoltaic system, the battery is popularly used as energy storage. Whereas, the dynamic external environmental factors lead to the solar arrays with non-linear output characteristics, which seriously affect the lifespan of the batteries.